Increasing Student's Thinking Creativity Through Project Based Learning - Muhammad Mushfi El Iq Bali; Selvi Ika Damayanti (Al-Fikru: Jurnal Ilmiah, 2023)
Various strategies can increase students' creative thinking. One of them is a project-based learning strategy. However, in practice, only a few teachers succeeded, especially in implementation procedures. Therefore this study aims to analyze the implementation of learning using project-based learning strategies to increase students' creative thinking. This research was conducted in class 4 SDN Kebonagung II Kraksan Probolinggo. The research method used is case study-based qualitative. Teacher and student research informants. Data analysis uses Miles and Huberman techniques which consist of data collection, data reduction, data presentation, and conclusion. The research results show that. This strategy is implemented by completing a project; students present their findings to other students. To see its success, it describes the initial conditions before implementing the strategy: less than optimal learning and student creativity that still needs to be higher. For this reason, learning is carried out through group discussions and project work. The condition ultimately increases student creativity; this can be seen in the ability of students to express ideas that are in students minds. The research results have implications for improving student learning outcomes.